Essays on the Economic Analysis of Tort Law - Guerra, Alice <1988> (Alma Mater Studiorum - Università di Bologna, 2015)
The analysis of tort law is one of the most influential and extensively developed applications of the economic approach in the study of law. Notwithstanding the exhaustive number of contributions on tort law and economics, several open questions remain that warrant further investigation. The general aim of this research project is to refine the traditional model of tort law in order to make it more realistic, updated with the recent technological progress and in line with the experimental results concerning prosocial behavior. This book is divided into six chapters: Chapters 1 and 6 provide an introduction and conclusions, respectively, while the remaining chapters are written in the form of separate yet related articles.